(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
New biostratigraphic data on the Frazzanò Flysch Formation are presented. This unit is the topmost formation of the stratigraphic succession characterizing the Longi-Taormina Unit, which in turn represents the lowest tectonic unit of the Peloritani Mountains and the only unit in the entire southern sector of the Calabria-Peloritani Arc in which cenozoic terrains have been recognized. The age of the Frazzanò Fm., which as yet has not been well defined, is essential to ascertain the time period during which the tectogenetic phase responsible for the stacking (superposition) of the nappes in the Peloritani Mountains occurred . Coltro (1967) reported foraminiferal assemblages of Late Eocene age, but subsequently ages ranging between the Middle Eocene and the Oligocene have been pro posed, none of them supported by new biostratigraphic data. The identification of some coccolithid taxa which appear in the Late Oligocene and Early Miocene allowed us to attribute an age not older than Upper Oligocene to the levels that mark the transition between the Frazzanò Fm.and the underlying Militello Formation, and an age not older than Early Aquitanian to the most recent beds of the Frazzanò Formation. Therefore, the tectogenetic phase responsible for the superposition of the nappes in the Peloritani Mountains, very likely started during the Aquitanian. While these data agree with the evolution of homologous units recognised in the Betic and Rifian sectors, they challenge the Late Oligocene age ascribed to the basal levels of the Stilo-Capo d’Orlando Formation, which lies unconformably over all the tectonic units of the Calabria-Peloritani Arc and pro vides a chronological upper limit to their overthrusting.